1995
DOI: 10.1097/00041433-199508000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein (a) and coronary heart disease

Abstract: Elevated Lipoprotein(a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(49 citation statements)
references
References 0 publications
0
47
0
2
Order By: Relevance
“…These can explain partially the impairment of endothelial-dependent arterial dilation in people with the e4 allele. Lp(a) is an independent risk factor for atherosclerotic vascular disease [25,26]. Many prospective studies have shown that excess Lp(a) is associated with premature coronary atherosclerosis and risk of cardiovascular disease [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…These can explain partially the impairment of endothelial-dependent arterial dilation in people with the e4 allele. Lp(a) is an independent risk factor for atherosclerotic vascular disease [25,26]. Many prospective studies have shown that excess Lp(a) is associated with premature coronary atherosclerosis and risk of cardiovascular disease [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…These hypothetical cooperative effects of Lp(a) and LDL in lesions could be related to the observed additive effect of these 2 apoB lipoproteins as risk factors for atherosclerotic disease. 41 …”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the plasma levels of Lp(a) as well as the size of apo(a) are independent risk factors for CAD and strokes [69][70][71][72][73][74][75][76] . Several atherogenic properties of Lp(a) have been clarified 78,79) .…”
Section: ) Lp(a)mentioning
confidence: 99%